Pengaruh Kegiatan Mewarnai Gambar terhadap Kemampuan Motorik Halus Anak TK Kelompok B - Nurhayati Nurhayati (Aṭfāluna: Journal of Islamic Early Childhood Education, 2020)
The purpose of this study was to determine the effect of colouring pictures on the fine motor skills of children in Group B of TK Negeri Pembina Labuan, with a sample of 17 children enrolled in the 2018/2019 school year. The indicators observed were speed, strength and accuracy. The results of the study are there are effects of colouring pictures on children's fine motor skills through the application of one-group pretest-posttest design, as evidenced by the development of fine motoric children from an average of 19.6% before treatment to 27.44% after treatment for the Very Developing category Good, from 25.48% to 27.44% the Developing Category Appropriate As Expected, from 23.52% to 29.40% the Start Developing category, and from 31.37% to 15.68% the Not Developing category. Based on the results of the study, it can be concluded that there is an influence of the activity of colouring pictures on the fine motor skills of children in Group B of TK Negeri Pembina Labuan.